Demographic characterization of canines and felines in four neighborhoods of southern Montería, Colombia - Pardo, Enrique (2025)
The aim of the study was to describe the demographic characteristics of the population of dogs and cats residing in four neighborhoods in the south of the city of Montería, Colombia. It was carried out under the descriptive model, applying house-to- house surveys. Data was collected on households with pets, breed, age and sex of pets, person/pet ratio, reason for ownership, type of food, and vaccination and deworming status. Of the 568 households sampled, 83% had at least one pet, 51.8% between 1 and 5 years of age, with 73% being male in dogs and 53% female in cats. The person/pet ratio was 4.4:1 and 10:1 for dogs and cats, respectively. The main reason for pet ownership was affection (>72%). Regarding the type of food, dogs and cats were fed with commercial food (71.1 and 70.1%, respectively), Creole breeds predominated (72.2 and 70.2% for dogs and cats, respectively) and with respect to health care, 59.7% (dogs) and 76.1% (cats) were dewormed, while 79.7% (dogs) and 80.2% (cats) were vaccinated.